2009
DOI: 10.1557/jmr.2009.0349
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and energy storage capability of antiferroelectric Pb0.92La0.08Zr0.95Ti0.05O3 film-on-foil capacitors

Abstract: Antiferroelectric (AFE) Pb0.92La0.08Zr0.95Ti0.05O3 (PLZT) films were grown on nickel foils with lanthanum nickel oxide buffer by chemical solution deposition. We observed field-induced AFE-to-ferroelectric (FE) phase transition. The electric field for the AFE-to-FE phase transition (EAF ≈ 270 kV/cm) and that for the reverse phase transition (EFA ≈ 230 kV/cm) were measured at room temperature on samples with PLZT films of ≈1-µm thickness. Relative permittivity of ≈560 and dielectric loss of <0.05 were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
77
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 11 publications
1
77
1
Order By: Relevance
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Antiferroelectrics (AFEs) form a class of important materials that are currently receiving a lot of attention, mainly because they are promising candidates for obtaining high-density energy storage [1][2][3][4][5] . They are also fundamentally challenging and interesting, as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the energy density values already found in thin film electroceramic capacitors. These are typically $15 Jcc À1 or greater, [13][14][15][16] with energy densities as high as 53 Jcc À1 reported 17 (compare with bulk values given above).…”
mentioning
confidence: 96%